Pengaruh Label Halal, Kebutuhan, Dan Literasi Keuangan Terhadap Keputusan Pembelian Kosmetik Pada Mahasiswa Di Perguruan Tinggi Kabupaten Sorong - Atina Melinda.A; andi hasrun; Vantri Pieter Kelelufna (Prodi Ekonomi Syariah IAIN Sorong, 2025)
This study aims to determine the influence of halal labels, needs, and financial literacy on cosmetic purchasing decisions among college students in Sorong Regency. The study used a quantitative method with a descriptive approach. The study sample consisted of 95 respondents, namely active college students at universities in Sorong Regency who regularly use cosmetics. Data were collected through a Google Form and analyzed using multiple linear regression. The results showed that halal labels did not influence consumer purchasing decisions for cosmetic products, with a calculated t-value < t-table (0.224 < 1.986). Similarly, needs did not influence purchasing decisions (calculated t-value < t-table: 0.267 < 1.986). Conversely, financial literacy significantly influenced consumer purchasing decisions for cosmetic products, as evidenced by a calculated t-value > t-table (7.680 < 1.986).